Generation and Phenotypic Analysis of a Transgenic Line of Rabbits Secreting Active Recombinant Human Erythropoietin in the Milk - Mikus, Tom s; Poplstein, Martin; Sedl kov, Jirina; Landa, Vladim r; Jen kov, Gabriela; Trefil, Pavel; Lidick, Jan; Mal, Petr (Transgenic research, 2004)
Production of recombinant human erythropoietin (rhEPO) for therapeutic purposes relies on its expression in selected clones of transfected mammalian cells. Alternatively, this glycoprotein can be produced by targeted secretion into the body fluid of transgenic mammals. Here, we report on the generation of a transgenic rabbits producing rhEPO in the lactating mammary gland. Transgenic individuals are viable, fertile and transmit the rhEPO gene to the offspring. Northern blot data indicated that the expression of the transgene in the mammary gland is controlled by whey acidic protien (WAP) regulatory sequences during the period of lactation. While the hybridization with total RNA revealed the expression only in the lactating mammary gland, the highly sensitive combinatory approach using RT-PCR/hybridization technique detected a minor ectopic expression. The level of rhEPO secretion in the founder female, measured in the period of lactation, varied in the range of 60-178 and 60-162 mIU/ml in the milk and blood plasma, respectively. Biological activity of the milk rhEPO was confirmed by a standard [3H]-thymidine incorporation test. Thus, we describe the model of a rhEPO-transgenic rabbit, valuable for studies of rhEPO glycosylation and function, which can be useful for the development of transgenic approaches designed for the preparation of recombinant proteins by alternative biopharmaceutical production.